Prediction of Love Stories and Love Styles based on Early Maladaptive Schemas - M. Karami; F. Mohsenzadeh, Ph.D.; K. Zahrakar, Ph.D. (خانواده و پژوهش, 2021)
The purpose of this research was to predict love stories and love styles based on early maladaptive schemas. The research method was descriptive and correlational. The statistical population comprised all married teachers in Tehran (Districts 2 and 5) in school year 2018-19. Random multi-stage cluster sampling method was utilized and 300 teachers were selected. The instruments consisted of Young Schema Questionnaire-Short Form (2005), Sternberg Love Story Scale (2001), and Lee Love Attitude Scale (1986). Pearson correlation coefficient and multivariate regression were utilized to analyze the data. Results showed that there was a significant relationship between early maladaptive schemas, love stories, and love styles. Moreover, early maladaptive schemas can predict love stories and love styles. Accordingly, it can be stated that types of schema have an impact on the formation of love stories and love styles based on which individuals choose their partners.